Stakeholder’s Role, Cash Slack and Sustainability Report on Stock Investment Decisions: Experimental Study - Jesica Handoko; Sihar Tigor Benjamin Tambunan; Ceicilia Bintang Hari Yudhanti (Universitas Pendidikan Ganesha, 2025)
The current research aims to prove whether independent variables stakeholder’s role, cash slack and sustainability reports have an influence on stock investment decisions from stakeholders. 2x2x2 between-subjects experimental design is conducted to test the hypothesis. The study involved private sector employees and undergraduate students related with Accounting major, serving as representatives for employees and investors. Out of the participants, 84 successfully completed the manipulation check questions, and their responses were analyzed to test the research hypothesis. The results indicate that stakeholders significantly impact stock investment decisions. There is also an interaction between the role of stakeholders and sustainability reports on stock investment decisions. However, there were no direct of interaction effect of cash slack on these decisions. These outcomes suggest that stakeholders interpret the information provided by management in varied ways, highlighting the need for management to foster alignment among different parties.